2013
DOI: 10.1037/a0032688
|View full text |Cite
|
Sign up to set email alerts
|

The impact of individual, competitive, and collaborative mathematics game play on learning, performance, and motivation.

Abstract: The present research examined how mode of play in an educational mathematics video game impacts leaming, performance, and motivation. The game was designed for the practice and automation of arithmetic skills to increase fluency and was adapted to allow for individual, competitive, or collaborative game play. Participants (N = 58) from urban middle schools were randomly assigned to each experimental condition. Results suggested that, in comparison to individual play, competition increased in-game leaming, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(157 citation statements)
references
References 89 publications
5
148
2
2
Order By: Relevance
“…A passive style of game, which did not provide meaning was less effective than game styles that utilized mental preparation and consideration. Plass, et al (2013) found that although competitive nature of game-style learning activities did not have a noticeable trend in outcome, it did have a positive effect for a mastery goal orientation for learning. A study conducted on 58 eighthgrade students showed that there was an increase in mastery goal orientation toward learning when the game featured competition and collaboration (Plass, et.…”
Section: Literature Reviewmentioning
confidence: 98%
“…A passive style of game, which did not provide meaning was less effective than game styles that utilized mental preparation and consideration. Plass, et al (2013) found that although competitive nature of game-style learning activities did not have a noticeable trend in outcome, it did have a positive effect for a mastery goal orientation for learning. A study conducted on 58 eighthgrade students showed that there was an increase in mastery goal orientation toward learning when the game featured competition and collaboration (Plass, et.…”
Section: Literature Reviewmentioning
confidence: 98%
“…These results have remained the same for every area of the educational curriculum, and very especially, for mathematics Hossain & Tarmizi, 2013;Lehrer & Lesh, 2013;Plass et al, 2013;Slavin & Lake, 2009;Suri, 2010), being this particular area of knowledge one of the most prolific in both manuals and compilations published (Davidson, 1990a;Sities & Buethe, 2010;Strebe, 2010), as well as in the different research carried out, something which has resulted in numerous research reports and hundreds of scientific and informative publications (Eisenhauer, 2007;Kagan & Kagan, 2005;Slavin et al, 2013).…”
Section: Introductionmentioning
confidence: 51%
“…Therefore, collaboration is more than just an ensemble of students put together in a group. Collaboration is important for students' social, cognitive, academic and adaptive thinking developments (Plass et al, 2013). The analysis of curricula documents shows that this principle has unfortunately been largely neglected.…”
Section: Collaborationmentioning
confidence: 99%